Employability competencies of South African Human Resource Development graduates - Chweu, G.; Schultz, C.; Jordaan, C. (South African Journal of Higher Education, 2023)
Higher education institutions are not properly prepared to meet the expectations of employers regarding the work readiness of human resource development (HRD) graduates from universities. Employers seek to recruit graduates who have pertinent employability competencies. The factors that were determined should contribute considerably to meeting this need. The study was commenced to identify the factors relating to employability competencies for South African human resource development graduates. The sample of the survey comprised 134 professionals from the South African Board of People’s Practice (SABPP) in the nine (9) provinces of South Africa. A factor analysis was employed to identify the issues relating to the employability competencies of HRD graduates. Correlation analysis and regression analysis were used to establish the relationships between identified factors. The results confirmed that there were strong relationships between the factors of the current and the expected competencies concerning the employability of South African HRD graduates. The findings served to formulate specific recommendations on employers’ expectations regarding the employability competencies of HRD graduates. The intention of the study was to improve graduates’ competencies in the world of work.